Tokatlı Ishâk Efendi and his Mathnawis named Nazmu'l-Le?ali - (:unkn) unknown (My University, 2015)
Bu çalışmada, Tokatlı İshâk Efendi'nin XVII. yüzyılda kaleme aldığı Nazmu'l-Le?aliadlı dinî mesnevisi hakkında bilgi verilmektedir. İshâk Efendi, Tokat'ta yetişmiş önemli âlim şairlerden biridir. Müellifin çoğu eseri medreselerde ders kitabı olarak okutulmuş, bu eserlerden bazıları elden ele dolaşarak birçok yazma nüshası oluşturulmuştur. Çok beğenilen eserlerinden biri olan Nazmu'l-Le?ali aruz vezninin canlı ve hareketli bir bahri onan hezecin "Mefa?ilün Mefa?ilün Fa?ulün"kalıbıyla yazılmıştır. Mesnevide akâid konuları ayrı ayrı ele alınarak işlenmiştir. Ayrıca hak yoldan çıkmış mezhepler, kabir azabı, Hz. Peygamber'in miracı, melekler gibi konular ayrı başlıklar hâlinde açıklanmıştır. Nazmu'l-Le?ali'nin "Hâtime" bölümünde müellif, halkın perişanlığını, vurguncuların köylerde, kasa- balarda ve şehirlerde kol gezdiğini, Budin Kalesi gibi muhkem bir kaleye sahip Tokat şehrinin bile bu yağmacıların eline geçtiğini etkili bir üslupla anlatmıştır.

In this study, we will give information about Nazmu'lLe'âl by Tokatlı İshâk Efendi. Versification masnavi was commonly used in Turkish literature in the seventeenth century, almost every poet wrote works as in this verse. Now this century, Addition to the usual masnavi issues, indigenous issues began to be processed. Indeed, in this century, such as held at, hilyes, forty hadith translations, many masnavi written on religious subjects. In the wake of our researches, we found out that these catechisms in verse constitute a notable part of our religious literature. This fact incited us to study how this tradition emerged. Hereby study is about one of source texts and its translations in verse, which is highly influential for emergence of the tradition. We introduce two poetic translations of the work, in order to better reflect its referential value. Evidently, the texts, which influenced the emergence of mentioned tradition, are not limited with this prose work, but we consider it important in regard to influential extent of the book. Besides, we believe that newly discovered catechisms in verse, as well as other religious literary genres, will help for better comprehension regarding the content and limits of our literature.In our view, it will be useful to introduce two prose works below, which we consider as the basis of poetic catechisms, as translations in verse, since the two following works are among the pieces to constitute an origin for beginning of a tradition. We are working on a religious masnavi named Nazmu'l-Leal's written in this century. Akaid issues in Masnavi were separately explained
Tokatlı İshâk Efendi ve Nazmu'l-Le?ali Adlı Mesnevisi
Keywords: Edebiyat